The LEGAL PROTECTION FOR CONSUMER OF DRUG PRODUCER THAT DOES NOT HAVE A DISTRIBUTION PERMIT FROM THE FOOD AND DRUG CONTROL AGENCY (BPOM) - Hendra Lazuardi; Nur Handayati (Transpublika Publisher, 2023)
For maintain health in carrying out daily activities, humans consume drugs as a healing solution for the ailments they experience. However, cases of illegal drug distribution threaten the health of someone who accidentally consumes illegal drugs without testing by the Food and Drug Monitoring Agency. The purpose of this research is to analyze the process of granting licenses to the distribution of drugs by BPOM and legal protection for consumers against the distribution of drugs that do not have distribution permits. This type of research is normative legal research with the Statue and Case Approach. Analysis data used descriptive qualitative analysis of existing laws and regulations to find answers to cases of drug trafficking that do not have a distribution permit. The results of the study prove that the process of granting permits for drug distribution by BPOM is carried out in two stages, namely the Pre-registration and Registration stages with the fulfillment of the required statements and documents. The evaluation process is carried out for 100 days for new drug products which is carried out by the Head of the BPOM Agency. Legal protection for consumers against the distribution of drugs that do not have a distribution permit is by imposing a maximum imprisonment of 15 years and a maximum fine of IDR 1,500,000,000.00 for the perpetrator. For producers who do not have the expertise and authority to carry out pharmaceutical practices, they will be fined a maximum of IDR. 100,000,000.00.